Headlice in schoolchildren from Ciudad Bolívar, Bolívar state, Venezuela - Rodolfo Devera; Ytalia Blanco; José Nastasi-Miranda; Deisi Duerto; Delci Figuera; Vicmar González; Raquel Guevara; Katherine Hernández; Yasvict Lanza; María Taboada (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2015)
Between April and July 2013 a cross sectional study was conducted to determine the prevalence of headlice in children aged 6-15 years enrolled in four schools in Ciudad Bolívar, Bolivar State, Venezuela. The parasitological diagnosis was made by direct observation of eggs, nymphs and/or adults on the scalp and/or hair. After signing the informed consent, we filled a clinical and epidemiologic record to each participant. 697 children (40.3%) of the 1730 school enrollment were evaluated, determining a prevalence of 25.1% (175/697). Girls were significantly more infected (42.4%) (OR: 9.35 p<0.05). All age groups were affected (χ2 (Yates correction) = 6.90 d.f.: 4 p> 0.05), but the group of 8-11 years was predominant (70.3%). Factors associated with a higher prevalence of headlice were female (OR: 9.35 p<0.05), having previously had the disease (OR: 5.76 p<0.05) and have long hair (OR: 7.12 p<0.05) and dirty (OR: 2.20 p<0.05). In conclusion, although the headlice prevalence was relatively low (25.1%), we verified that this parasitoses remains a major medical problem in schoolchildren in Ciudad Bolivar.